Origins and Evolution of WUSCHEL-Related Homeobox Protein Family in Plant Kingdom - Gaibin Lian; Zhiwen Ding; Qin Wang; Dabing Zhang; Jie Xu (The Scientific World Journal)
WUSCHEL-related homeobox (WOX) is a large group of transcription factors specifically found in plants. WOX members contain the conserved homeodomain essential for plant development by regulating cell division and differentiation. However, the evolutionary relationship of WOX members in plant kingdom remains to be elucidated. In this study, we searched 350 WOX members from 50 species in plant kingdom. Linkage analysis of WOX protein sequences demonstrated that amino acid residues 141–145 and 153–160 located in the homeodomain are possibly associated with the function of WOXs during the evolution. These 350 members were grouped into 3 clades: the first clade represents the conservative WOXs from the lower plant algae to higher plants; the second clade has the members from vascular plant species; the third clade has the members only from spermatophyte species. Furthermore, among the members of Arabidopsis thaliana and Oryza sativa, we observed ubiquitous expression of genes in the first clade and the diversified expression pattern of WOX genes in distinct organs in the second clade and the third clade. This work provides insight into the origin and evolutionary process of WOXs, facilitating their functional investigations in the future.